METHODOLOGICAL APPROACHES TO COMPETITIVENESS ASSESSMENT BUSINESS ENTITIES - Зелінська, Галина Олексіївна; Андрусів, Уляна Ярославівна; Микитюк, Наталія Євгенівна; Михайлюк, Юрій Романович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2024)
The purpose of the article is to substantiate the theoretical and methodological principles and develop practical recommendations for the formation and improvement of the competitive advantages of economic entities using factor analysis. This method makes it possible to identify key factors that affect the competitiveness of economic entities, as well as to determine their importance. The article highlights the theoretical foundations of the formation of competitive advantages of economic entities. It has been established that assessing the competitiveness of business entities is an important stage in business management. Competitiveness is determined by the ability of business entities to compete effectively on the market, providing high quality products or services, competitive prices, innovative solutions and excellent customer service. Methodical approaches to managing the competitiveness of economic entities have been formed, which will allow them to understand and determine their competitive advantages and disadvantages, as well as to develop a strategy to increase their competitiveness in the market. The organizational and economic measures to increase the competitive advantages of the business entities of the complex are substantiated. It is substantiated that the integrated corporate structure aims to create favorable conditions for increasing the competitiveness of economic entities by optimizing internal business processes, resources and management. The proposed theoretical directions make it possible to draw more reasonable conclusions about the state of competitiveness of economic entities and will contribute to the adoption of managerial decisions regarding the improvement of certain aspects of their activity. The analysis of the obtained results will allow to identify problem areas, to determine the priority areas of development and to develop specific measures for their solution. Thus, research helps business entities to focus on key aspects of their activities and achieve effective results in a competitive environment.